Fatty Acid Biosynthesis in Mitochondria of Grasses: Malonyl-Coenzyme A Is Generated by a MitochondrialLocalized Acetyl-Coenzyme A Carboxylase - Focke, Manfred (The American Society for Plant Biologists, 2003)
We present biochemical evidence for the occurrence of a 250-kD multifunctional acetyl-coenzyme A carboxylase in barley (Hordeum vulgare) mitochondria. Organelles from 6-d-old barley seedlings were purified by differential centrifugation and Percoll density gradient centrifugation. Upon analysis by two-dimensional Blue-native (BN)/SDS-PAGE, an abundant 250-kD protein can be visualized, which runs at 500 kD on the native gel dimension. A similar 500-kD complex is present in etioplasts from barley. The mitochondrial 250-kD protein is biotinylated as indicated by specific reaction with an antibody directed against biotin. Peptide sequence analysis by electrospray ionization tandem mass spectrometry of the 250-kD proteins from both organellar fractions revealed amino acid sequences that are 100% identical to plastidic acetyl-coenzyme A carboxylase from wheat (Triticum aestivum). The 500-kD complex was also detected in wheat mitochondria, but is absent in mitochondrial fractions from Arabidopsis. Specific acetyl-coenzyme A carboxylation activity in barley mitochondria is higher than in etioplasts, suggesting an important role of mitochondria in fatty acid biosynthesis. Functional implications are discussed.